The assignment of Prodidactidae to Hyblaeoidea, with remarks on Thyridoidea (Lepidoptera) - Kaila, Lauri; Epstein, Marc E.; Heikkilä, Maria; Mutanen, Marko (Zootaxa, 2013)
We examine the systematic position of the lepidopteran family Prodidactidae Epstein and Brown, 2003, which includes the single species Prodidactis mystica (Meyrick). We provide details on a morphological trait of the adult male hindcoxa that appears to link Prodidactidae with Hyblaeidae. This putative relationship is consistent with molecular data derived from five genes. Based on morphological and molecular evidence, we place Prodidactidae in Hyblaeoidea. Moreover, the apex of the larval spinneret is similarly modified in these families and in Thyrididae. This modification is unknown in other Lepidoptera and may prove to be a synapomorphy linking Thyridoidea and Hyblaeoidea. As the latter is not fully congruent with published molecular studies, we refrain from suggesting sister group position for Thyridoidea and Hyb-laeoidea.